Intermittent fasting – a novel approach to treating overweight and obesity? – meta-analysis and literature review - Lubczyńska, Zuzanna; Popravko, Yevheniia; Lewandowski, Mateusz Mirosław; Bienia, Grzegorz; Żołnierek, Maja; Świętochowski, Jakub; Siekierko, Nikola; Kotusiewicz, Wiktoria; Jędrzejewska, Barbara; Kotulska, Maria (Journal of Education, Health and Sport, 2023)
Introduction Intermittent fasting (IF) is a form of dietary intervention that includes periods of regular calorie intake alternated with periods of fasting. IF has gained a lot of attention as a potential approach to treating metabolic syndrome-related diseases. Therefore, health care professionals need to be able to provide their patients with evidence-based information on IF. The aim of this article is to review data on effectiveness of IF in weight loss, especially in comparison with calorie restriction. Methods PubMed and Google Scholar databases were searched for studies published from 1.01.2017 to 31.12.2022 that included phrases “intermittent fasting” or “alternate day fasting”, “intermittent fasting obesity”, “alternate day fasting obesity”. Intervention studies on obese or overweight patients were included. We excluded studies of short duration and studies that focused on intercurrent medical conditions. In total, 14 articles that suited those criteria were identified. Results Intermittent fasting induces pronounced metabolic changes in the body due to strict and time-limited restriction of calorie intake and in animal models was proved to prolong lifespan and modulate tumorigenesis and aging. It is a proposed new approach to treating obesity, which is a a major risk factor for cardiovascular diseases and diabetes. Conclusions In our study, IF was found as effective, but not superior to calorie restriction in reducing body mass, improving body composition and reducing other cardiometabolic risk factors. Our findings are consistent with other recent systematic reviews. Further research is needed to directly compare various IF regimens and determine patients’ characteristics that may be associated with more successful implementation of intermittent fasting regimens.